Aerobic physical activity and resistance training: an application of the theory of planned behavior among adults with type 2 diabetes in a random, national sample of Canadians - Karunamuni Nandini; Trinh Linda; Courneya Kerry S; Plotnikoff Ronald C; Sigal Ronald J (BMC, 2008)
Abstract Background Aerobic physical activity (PA) and resistance training are paramount in the treatment and management of type 2 diabetes (T2D), but few studies have examined the determinants of both types of exercise in the same sample. Objective The primary purpose was to investigate the utility of the Theory of Planned Behavior (TPB) in explaining aerobic PA and resistance training in a population sample of T2D adults. Methods A total of 244 individuals were recruited through a random national sample which was created by generating a random list of household phone numbers. The list was proportionate to the actual number of household telephone numbers for each Canadian province (with the exception of Quebec). These individuals completed self-report TPB constructs of attitude, subjective norm, perceived behavioral control and intention, and a 3-month follow-up that assessed aerobic PA and resistance training. Results TPB explained 10% and 8% of the variance respectively for aerobic PA and resistance training; and accounted for 39% and 45% of the variance respectively for aerobic PA and resistance training intentions. Conclusion These results may guide the development of appropriate PA interventions for aerobic PA and resistance training based on the TPB.